2022
DOI: 10.3201/eid2802.211270
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Infection with Oz Virus, a Novel Thogotovirus

Abstract: Oz virus is a novel thogotovirus isolated from ticks that causes lethal infection in mice. We conducted serosurveillance of Oz virus infection among humans and wild mammals in Japan using virus-neutralization tests and ELISAs. Results showed that Oz virus may be naturally infecting humans and other mammalian hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Suffolk County deer seropositivity (66.5%) was higher than the seroprevalence reported in North Carolina deer (56%), but lower than deer harvested in Missouri (86%) (8, 9). BRBV seroprevalence rates of white-tailed deer harvested from various areas in Suffolk County (Table 2) were similar to Oz virus seroprevalence rates (30.0-73.7%) in wild sika deer ( Cervus nippon ) sampled from Japanese prefectures located nearest to the initial detection of the virus (3). The lower seroprevalence in regions of NY outside of Long Island is likely attributed to fewer established populations of A. americanum or incidental transmission by bird-dispersed immatures originating from established regions.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Suffolk County deer seropositivity (66.5%) was higher than the seroprevalence reported in North Carolina deer (56%), but lower than deer harvested in Missouri (86%) (8, 9). BRBV seroprevalence rates of white-tailed deer harvested from various areas in Suffolk County (Table 2) were similar to Oz virus seroprevalence rates (30.0-73.7%) in wild sika deer ( Cervus nippon ) sampled from Japanese prefectures located nearest to the initial detection of the virus (3). The lower seroprevalence in regions of NY outside of Long Island is likely attributed to fewer established populations of A. americanum or incidental transmission by bird-dispersed immatures originating from established regions.…”
Section: Discussionmentioning
confidence: 55%
“…Bourbon virus (BRBV, Orthomyxoviridae ; Thogotovirus ) is a suspected tick-borne human pathogen first isolated in 2014 from a patient that resided in Bourbon County, Kansas (1). BRBV is closely related to Oz virus, recently isolated from Amblyomma testudinarium ticks in Japan (2, 3). Since the initial discovery of BRBV, human cases have been identified in Kansas, Missouri, and Oklahoma (4).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In 2021, Kodama et al reported a novel tick-borne orthonairovirus named Yezo virus (YEZV) in Japan, associated with acute febrile, thrombocytopenia, and leukopenia [ 6 ]. As recently as in 2022, serosurveillance in Japan indicated that a novel tick-borne thogotovirus named Oz virus may naturally infect humans and some other mammals [ 7 ]. With increased sampling and development in detection techniques, more novel tick-borne human pathogens are still being discovered.…”
Section: Introductionmentioning
confidence: 99%
“…BRBV is the first Thogotovirus discovered in North America that is known to infect humans. Three other members of this genus, Thogotovirus, Oz virus and Dhori virus, which have not been found in the US, have been associated with human disease [23][24][25]. HRTV is also a segmented RNA virus that belongs to the family Bunyaviridae: genus Phlebovirus [26].…”
Section: Introductionmentioning
confidence: 99%